Bath Abbey
similar considerations crown the skyline at Bath Abbey-the last major Gothic building in the land. Built by Bishop Oliver King who had been instrumental as Secretary of State in establishing Henry VII, the first of the Tudor Kings on the throne, the new Abbey replaced a larger Norman building which had become ruinous. The west end is decorated with sculpture which includes the figures of angels ascending and descending Jacob's ladder. Other carving commemorates a vision in which a voice cried "Let an Olive establish the Crown and a King restore the Church.